2001
DOI: 10.1055/s-2001-15492
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Ipsilateral Congenital Diaphragmatic Pathologies: Rarities to Consider

Abstract: There are various postulated theories concerning the pathogenesis of ipsilateral pathologies during embryologic development of the diaphragm. Management of asymptomatic congenital eventrations remains debatable. However, when symptoms become apparent, ipsilateral defects though rare, should be considered and prompt surgical management through a thoracotomy or laparotomy approach is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Some diaphragmatic hernias have “sacs” which are thought to represent focal thinning of the diaphragmatic musculature. Thus the terminology “sac” hernia and eventration are poorly defined, and these entities may represent a continuum. A mixture of hernia types can occur as well, such as a typical posterolateral (Bochdalek) defect in one diaphragmatic leaflet, combined with an eventration in the contralateral leaflet or another portion of the ipsilateral leaflet [Akel and Nasr, 2001]. Although such a combination of defects is rarely seen, their true prevalence may not be known possibly due to underreporting.…”
Section: Classification Of Cdhmentioning
confidence: 99%
“…Some diaphragmatic hernias have “sacs” which are thought to represent focal thinning of the diaphragmatic musculature. Thus the terminology “sac” hernia and eventration are poorly defined, and these entities may represent a continuum. A mixture of hernia types can occur as well, such as a typical posterolateral (Bochdalek) defect in one diaphragmatic leaflet, combined with an eventration in the contralateral leaflet or another portion of the ipsilateral leaflet [Akel and Nasr, 2001]. Although such a combination of defects is rarely seen, their true prevalence may not be known possibly due to underreporting.…”
Section: Classification Of Cdhmentioning
confidence: 99%
“…It is still debated whether different types of diaphragmatic defects (e.g., a Bochdalek hernia vs. diaphragmatic eventration) are genetically distinct. Pathological studies have shown the presence of different types of diaphragmatic defects (Bochdalek hernias vs. eventration) in the same diaphragm leaflet or in different leaflets of the same diaphragm in isolated CDH [Akel and Nasr, 2001]. However, several studies of murine models of CDH involving loss of gene function have shown that the type of hernia associated with each mouse mutant is anatomically consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple diaphragm defects on the ipsilateral side have been reported previously in 6 patients [4]. Two patients were diagnosed as adults and had multiple defects in the central tendon of the right diaphragm.…”
Section: Discussionmentioning
confidence: 91%